3(1y+2y)=y+2y+4y

Simple and best practice solution for 3(1y+2y)=y+2y+4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1y+2y)=y+2y+4y equation:


Simplifying
3(1y + 2y) = y + 2y + 4y

Combine like terms: 1y + 2y = 3y
3(3y) = y + 2y + 4y

Remove parenthesis around (3y)
3 * 3y = y + 2y + 4y

Multiply 3 * 3
9y = y + 2y + 4y

Combine like terms: y + 2y = 3y
9y = 3y + 4y

Combine like terms: 3y + 4y = 7y
9y = 7y

Solving
9y = 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
9y + -7y = 7y + -7y

Combine like terms: 9y + -7y = 2y
2y = 7y + -7y

Combine like terms: 7y + -7y = 0
2y = 0

Divide each side by '2'.
y = 0

Simplifying
y = 0

See similar equations:

| 7z=119 | | 7x+6=4x-9 | | 5y+7=3y-13 | | 5x^2-11x-3=2x+3 | | 8m+28=4 | | 11-9c-4= | | x^2+5*x+4=0 | | 11-(9c-4)= | | 11a^2-32+17=20 | | b+7=11 | | 4x^2-46=3 | | 4x-1+3x=180 | | 9-(x-5)=41 | | 7m^2-2m=0 | | 1+4x=36 | | 9(x-5)=41 | | 5y-2(4x+2)= | | 5y-2(4x-2)= | | -20+5x=-4(3x-5)-6 | | x^3-25=103-x^3 | | 8x-1+4x+7=180 | | 6x+78=12+12 | | 24-3(6-3x)=2.25x | | 27=x^2+2x+y^2-12y | | 3x+27=5x-x-15 | | 3b+18=74 | | -n^2-11n-28=0 | | 68-4x=23x+17 | | 120-4x=4x+16 | | 4x+3x=96-x | | 47-6x=3x+17 | | 3x+4x+x=96 |

Equations solver categories